1-MNA Ameliorates High Fat Diet-Induced Heart Injury by Upregulating Nrf2 Expression and Inhibiting NF-κB in vivo and in vitro - Song, Ziguang; Zhong, Xiao; Li, Mingyang; Gao, Pingping; Ning, Zhongping; Sun, Zhiqi; Song, Xiang (Frontiers in Cardiovascular Medicine, 2021)
High levels of free fatty acids (FFA) are closely associated with obesity and the development of cardiovascular diseases. Recently, nicotinamide adenine dinucleotide (NAD) metabolism has emerged as a potential target for several modern diseases including diabetes. Herein, we explored the underlying mechanisms of NAD metabolism associated with the risk of cardiovascular disease. Our study found that nicotinamide N-methyltransferase (NNMT) mRNA levels were significantly increased in the hearts of FFA-bound-albumin-overloaded mice and in H9C2 cells treated with palmitic acid (PA). We studied the mechanisms underlining the anti-inflammatory and anti-oxidant activities of 1-methylnicotinamide (1-MNA), a metabolite of NNMT. We found a significantly higher level of reactive oxygen species, inflammation, apoptosis, and cell hypertrophy in PA-treated H9C2 cells and this effect was inhibited by 1-MNA treatment. In vivo, 1-MNA improved inflammation, apoptosis, and fibrosis damage in mice and this inhibition was associated with inhibited NF-κB activity. In conclusion, our study revealed that 1-MNA may prevent high fatty diet and PA-induced heart injury by regulating Nrf2 and NF-κB pathways.